Hydatid Cyst of Breast: A Case Report - Alam, F; Goel, RG (Journal of Nepalgunj Medical College, 2015)
Hydatid cyst is a zoonotic disease which occurs due to infectivity with larval stage of Echinococcus granulosus. The disease is chronic and cysts can be lodged in different organs. It has cosmopolitan distribution and impact health and economical challenges for many countries throughout the world. The location of the disease is mostly in the liver and lungs. Hydatid disease of breast is extremely rare. A case report of 24 year female with the diagnosis of the hydatid breast is described in detail. The patient presented with painless lump in the upper inner quadrant of right breast of two months duration. History of trauma, pus discharge, itching, weight loss, fever or hormonal therapy were absent. The patient was diagnosed preoperatively as cysticercosis right breast by fine needle aspiration cytology based on the laboratory results conducted outside the hospital. However, histopathology confirmed the diagnosis of hydatid breast. It is the second diagnosed case in Nepal. Therefore, accurate information on the distribution of the disease is first step for the control and prevention. Only few reports are published in the literature about breast hydatid cyst. Thus, we want to emphasize the importance of keeping hydatid disease in differential diagnosis of cystic breast lesions, particularly in endemic region, where the disease could mimic fibroadenoma, phyllodes tumors, chronic abscesses. Journal of Nepalgunj Medical College Vol.12(1) 2014: 41-42